Development of curcumin nanocrystal: Physical aspects. Issue 1 (9th October 2012) - Rachmawati, Heni; Shaal, Loaye Al; Müller, Rainer H.; Keck, Cornelia M.
Abstract Curcumin, a naturally occuring polyphenolic phytoconstituent, is isolated from the rhizomes of Curcuma longa Linn. (Zingiberaceae). It is water insoluble under acidic or neutral conditions but dissolves in alkaline environment. In neutral or alkaline conditions, curcumin is highly unstable undergoing rapid hydrolytic degradation to feruloyl methane and ferulic acid. Thus, the use of curcumin is limited by its poor aqueous solubility in acidic or neutral conditions and instability in alkaline pH. In the present study, curcumin nanocrystals were prepared using high‐pressure homogenization, to improve its solubility. Five different stabilizers [polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), d‐α‐tocopherol polyethylene glycol 1000 succinate (TPGS), sodium dodecyl sulfate (SDS), carboxymethylcellulose sodium salt] possessing different stabilization mechanism were investigated. The nanoparticles were characterized with regard to size, surface charge, shape and morphology, thermal property, and crystallinity. A short‐term stability study was performed storing the differently stabilized nanoparticles at 4°C and room temperature. PVA, PVP, TPGS, and SDS successfully produced curcumin nanoparticle with the particle size in the range of 500–700 nm. PVA, PVP, and TPGS showed similar performance in preserving the curcumin nanosuspension stability. However, PVP is the most efficient polymer to stabilize curcumin nanoparticle. This study illustrates that the developed curcumin nanoparticle held great potential as a possible approach to improve the curcumin solubility then enhancing bioavailability. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:204–214, 2013